A new method for predicting viscosity of pure organic liquids - (:unkn) unknown (Can Soc for Chem Eng, Ottawa, 1998)
A new semi-theoretical method based on Enskog's hard sphere theory for dense fluids and the principle of corresponding states is presented for predicting viscosity of pure organic liquids. The viscosities of 75 organic liquids -37 acyclic and 38 cyclic hydrocarbons - were calculated using this method which requires critical properties and normal boiling point as input data. The predictions were compared with empirical data and other prediction methods. Highly satisfactory results were obtained over a wide range of temperatures (0.45<Tr<0.80).A new semi-theoretical method based on Enskog's hard sphere theory for dense fluids and the principle of corresponding states is presented for predicting viscosity of pure organic liquids. The viscosities of 75 organic liquids - 37 acyclic and 38 cyclic hydrocarbons - were calculated using this method which requires critical properties and normal boiling point as input data. The predictions were compared with empirical data and other prediction methods. Highly satisfactory results were obtained over a wide range of temperatures (0.45 → Tr < 0.80).